(untitled) (Research, Society and Development, 2023)
The COVID-19 pandemic is an ongoing global health crisis caused by the spread of the SARS-CoV-2 virus, which was first identified in December 2019 in Wuhan, China. To analyze the main side effects reported by individuals after receiving the COVID-19 vaccines. For this study, the bibliographic research technique will be used, using bibliographic sources of the type of publications, found in articles and separate publications. The research is classified as bibliographic, as it is prepared based on already published material. The Pfizer-BioNTech and Moderna vaccines use messenger RNA (mRNA) and are highly effective against COVID-19, with mild side effects. AstraZeneca uses an adenovirus vector and has demonstrated efficacy, with rare cases of blood clots. Johnson & Johnson is a single dose and effective against severe cases, sharing common side effects. CoronaVac, inactivated, is effective in preventing serious cases, with similar side effects. All vaccines are safe, with differences in technologies and effectiveness. The choice depends on the availability and guidance of health authorities in the fight against COVID-19. In conclusion, the various COVID-19 vaccines play a vital role in containing the pandemic, sharing mild and temporary side effects. The choice of vaccine depends on availability and local public health guidelines, but all have been safe and effective in preventing serious cases, highlighting the importance of vaccination in individual and community protection.